THE NEGATIVE EFFECTS OF ETHNOCENTRISM IN MY BIG FAT GREEK WEDDING MOVIE - Riana Permatasari (Jurnal Penelitian Humaniora, 2019)
This study analyzes the negative effects of ethnocentrism in My Big Fat Greek Wedding movie by Joel Zwick. The data were in the form of dialogues and monologues collected by watching the movie, reading the script, identifying the data based on the research problem, and classifying the data.. Based on the findings, there are three negative effects of ethnocentrism shown by ethnocentric people. First, ethnocentrism builds a strong belief that their culture is superior to others. Second, ethnocentric people will perform high level of egocentrism. Third, ethnocentrism will affect inter-cultural communication in negative way. These three negative effects happen because ethnocentric people tend to focus only in group and evaluate other cultures based on their standards.